The University of Texas System TeleCampus: A Statewide Model for Collaboration - Hardy, Darcy W.; Robinson, Robert L. (International Review of Research in Open and Distributed Learning, 2002)
The University of Texas (UT) System has been meeting educational needs of students for over 150 years. In 1997, the UT System initiated the development of the UT TeleCampus, a centralized facilitation point for distance learning. The TeleCampus opened its virtual doors in May 1998, focused entirely on support services for students. By late 1998, the TeleCampus had begun developing what would become collaborative benchmark online programs for the UT System.As a result of having developed over 12 complete online degree programs since that time, many lessons have been learned about (1) barriers to collaboration and how to overcome them; (2) faculty development and interaction; and (3) the commitment required to build successful online programs.This article describes the UT TeleCampus initiative and how it has grown from a services-only organization to a nationally recognized model for delivering high quality distance education.